50 years and counting …. (1st January 2021) - Hanley, Jane
Abstract : The pandemic has made many of us reflect on the lives we enjoyed pre-Covid-19. Jane Hanley looks back on her career in health visiting and how the new year is a chance for the profession to move forward, using vital skills to make a difference